ANALISIS BEBERAPA FAKTOR YANG MEMPENGARUHI KEBIASAAN KONSUMEN UNTUK MEMBANDINGKAN HARGA DI TOKO SWALAYAN - FAUZIYAH HAYATI SYAHIR; LIES SUNARMINTYASWATI; NOVRITA ANDRIANA FITRI (Jurnal Bisnis dan Akuntansi, 2000)
The object of the study is to t st whether Indonesian (Jakarta especially) consumers behave the same is American consumers in price searching at supermarkets. It will also evaluate the reasons for their behavior. From previous research, it has been reported that consumers do price searching as a routine activity. Th author found there are four factors, which are: Economic return (Price perceived Dispersion); Search Cost (Mobility Constraint, Difficulty of Stor0 Comparison); Human Capital (Investment Search, Time Management Skills) and Psycosocial Returns (Shopping Enjoyment and Market Maven). From consumers which the authors met at supermarkets as respondents and their questionnaire answers, it was found that there are different dominant factors that influence consumers in America and in Jakarta to search price and to decide which supermarket they will choose and buy from.